3 - A Decade of Biomedical Research in West Africa (2005–14): A Bibliometric Analysis of the Ten Most Productive Countries in MEDLINE: by Williams Ezinwa Nwagwu - Nwagwu, Williams Ezinwa (Journal of Higher Education in Africa, 2022)
The objective of this research is to determine the quantity and quality of publications in biomedical research in top-producing countries in West Africa during 2005–14 as well as the characteristics of the journals and collaborative evidence in the area. Data was drawn from MEDLINE/ PubMed and Google Scholar while the impact factors of the journals were retrieved from the SCImago Journal and Country Rank portal. Quantity of publications was measured by counting the number of publications attributable to a country while h-index was extracted to measure quality. Productivity was analysed by sorting the data according to their first authors, journals and publication dates, and analysed using MS Excel and LOTKA®. Nigeria, Ghana, Senegal, Burkina Faso and Mali had the highest number of publications. In respect of productivity, apart from Côte d’Ivoire that had an α value less than 2, indicating a higher level of productivity, all other countries had an α value greater than 2. West African Journal of Medicine is the only journal of West African origin in the list of top ten journals where the authors from the sub-region published their papers, and it ranked tenth. Nigeria and Ghana published a lot more of their research papers in local journals in comparison with other countries, but these journals have very low mean impact factors. This study reinforces the need for improved research collaboration between the big and small countries.